Karl Marx og fortidens utopiske potentialer - Nygaard, Bertel (K&K - Kultur og Klasse, 2012)
KARL MARX AND THE UTOPIAN POTENTIALS OF THE PAST | Karl Marx explicitly situated modern emancipation struggles in the present rejecting the power of the past over the present along with utopian schemes for the future. But a closer study of his position reveals that his notion of the present was remarkably open towards aspects of the past and potentials for future alternatives, as long as these were conceived from – and as moments within – present struggles. Thus, his rejection of certain visions of past and future was mainly a critique of specific ideological configurations characteristic of modern bourgeois society, including reified notions of the past, history and temporality. From this critique we may derive a fruitful, discerning approach to the complex interrelations of utopia, ideology, past, present and future, founded on a critical reconstruction of the category of time as a differential social relation, persistently constructed and reconstructed through conflictual social agency.